ALK‐positive primary cutaneous T‐cell‐lymphoma (CTCL) with unusual clinical presentation and aggressive course. (25th June 2015) - Wehkamp, Ulrike; Oschlies, Ilske; Nagel, Inga; Brasch, Jochen; Kneba, Michael; Günther, Andreas; Klapper, Wolfram; Weichenthal, Michael
Abstract : Anaplastic lymphoma kinase (ALK) expression is uncommon in primary cutaneous T‐cell‐lymphomas (CTCL). We report the case of a patient who was initially diagnosed with small plaque parapsoriasis, and eventually developed an unusual manifestation of CTCL 6 years later. The disease was characterized by aggressively ulcerating plaques and tumors of the entire skin. Histopathology revealed monoclonal proliferation of atypical T‐lymphocytes and CD30‐positive blasts with expression of ALK and identification of an ATIC‐ALK fusion protein. Extensive staging confirmed the primary cutaneous origin of the lymphoma. After failure of several conventional treatments including polychemotherapy, the patient finally achieved remission after receiving brentuximab‐vedotin, alemtuzumab and subsequent allogeneic stem cell transplantation. In the following, the patient developed inflammatory cutaneous lesions that pathologically showed no evidence for lymphoma relapse or classical cutaneous graft‐versus‐host disease. The patient responded to immunosuppression, but finally died from multi‐organ failure due to sepsis 8 months after stem cell transplantation. This is a rare instance of ALK positivity in a CTCL, most likely resembling CD30+ transformed mycosis fungoides, because it was not typical for cutaneous anaplastic large cell lymphoma (ALCL). In contrast to its role in systemic ALCL as favorable prognostic marker, ALK expression here was associated with an aggressive course.